BECCS potential in Brazil: Achieving negative emissions in ethanol and electricity production based on sugar cane bagasse and other residues. (1st October 2016) - Moreira, José Roberto; Romeiro, Viviane; Fuss, Sabine; Kraxner, Florian; Pacca, Sérgio A.
Highlights: Demonstrates the cost competitiveness of sugarcane based bioenergy carbon capture and storage (BECCS). Evaluates BECCS based on emissions from sugar fermentation, which is the low hanging fruit technology available. Determines the BECCS cost premium of CO2, ethanol and electricity. Determines the full mitigation potential of this BECCS technology in Brazil. Discusses polices to enable BECCS deployment by society. Abstract: Stabilization at concentrations consistent with keeping global warming below 2 °C above the pre-industrial level will require drastic cuts in Greenhouse Gas (GHG) emissions during the first half of the century; net negative emissions approaching 2100 are required in the vast majority of current emission scenarios. For negative emissions, the focus has been on bioenergy with carbon capture and storage (BECCS), where carbon-neutral bioenergy would be combined with additional carbon capture thus yielding emissions lower than zero. Different BECCS technologies are considered around the world and one option that deserves special attention applies CCS to ethanol production. It is currently possible to eliminate 27.7 million tonnes (Mt) of CO2 emissions per year through capture and storage of CO2 released during fermentation, which is part of sugar cane-based ethanol production in Brazil. Thus, BECCS could reduce the country's emissions from energy production by roughly 5%. Such emissions are additional to those due to the substitution of biomass-based electricity for fossil-fueled power plants. This paper assesses the potential and cost effectiveness of negative emissions in the joint production system of ethanol and electricity based on sugar cane, bagasse, and other residues in Brazil. An important benefit is that CO2 can be captured twice along the proposed BECCS supply chain (once during fermentation and once during electricity generation). This study only considers BECCS from fermentation because capturing such CO2 is straightforward, thus potentially representing a cost-effective mitigation option for Brazil compared to other alternatives. The assessment shows that fuel prices would increase by less than 3.5% due to the adoption of BECCS from fermentation, while increasing investors' revenues are sufficient to compensate for the investment required. With appropriate government subsidies, or by sharing BECCS costs between all car fuels and all electricity supplied by hydro and bioelectricity, the increment in ethanol and electricity prices could be less than 1% for the final consumer. Meanwhile it would supply 77.3% of all cars' fuel (private cars) and 17.9% of all electricity in Brazil.